2002
DOI: 10.1128/jvi.76.19.9724-9734.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 (HIV-1) Accessory Protein Vpr Induces Transcription of the HIV-1 and Glucocorticoid-Responsive Promoters by Binding Directly to p300/CBP Coactivators

Abstract: The accessory Vpr protein of human immunodeficiency virus type 1 (HIV-1) is a promiscuous activator of viral and cellular promoters. We report that Vpr enhances expression of the glucocorticoid receptor-induced mouse mammary tumor virus (MMTV) promoter and of the Tat-induced HIV-1 long terminal repeat promoter by directly binding to p300/CBP coactivators. In contrast, Vpr does not bind to p/CAF or to members of the p160 family of nuclear receptor coactivators, such as steroid receptor coactivator 1a and glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 64 publications
1
98
0
Order By: Relevance
“…Recently a glucocorticoid receptor complex was identified as an intracellular target for Vpr (58,59) suggesting their possible involvement in Vpr-(52-96)-induced apoptosis. The observations that both glucocorticoids (60) and Vpr inhibited NFB induction suggest a role for glucocorticoid receptors in Vpr-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a glucocorticoid receptor complex was identified as an intracellular target for Vpr (58,59) suggesting their possible involvement in Vpr-(52-96)-induced apoptosis. The observations that both glucocorticoids (60) and Vpr inhibited NFB induction suggest a role for glucocorticoid receptors in Vpr-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that Vpr behaved as an adaptor molecule between promoter-bound transcription factors and p300/CBP coactivators in a glucocorticoid-responsive promoter (42). We also reported that nuclear receptor-responsive promoters employed the same set of coactivators and transcription-elongation complexes as the HIV-1 long terminal repeat, and that Vpr potentiated both types of promoter activities through the same mechanism, cooperating with host coactivators (43).…”
mentioning
confidence: 63%
“…Vpr can induce several promoters, including the HIV-1 LTR and p21 WAF1 (Wang et al, 1995;Amini et al, 2004). These studies suggest that cooperativity between several cellular proteins including Sp1 (Wang et al, 1995), p300 (Kino et al, 2002) and p53 (Sawaya et al, 1998) is necessary for Vpr-induced regulation of the HIV-LTR. Vpr was also shown to cause cell differentiation and DNA damage (Shimura et al, 1999a, b).…”
Section: Introductionmentioning
confidence: 78%